Ceropegia gilboaensis (Apocynaceae), a new species from the Midlands of KwaZulu-Natal, South Africa - Heiduk, Annemarie; Crouch, Neil R.; Styles, David G.a. (Phytotaxa, 2023)
A new species of Ceropegia (Apocynaceae-Asclepiadoideae-Ceropegieae), C. gilboaensis, is described from the Midlands of KwaZulu-Natal, South Africa, where it occurs along exposed rock sheets in Midlands Mistbelt Grassland. This new tuberous species, which lacks the tubular trap-flowers typical of Ceropegia s.str., is assigned to section Chamaesiphon. Ceropegia gilboaensis is vegetatively and floristically most similar to C. ngomensis (formerly Brachystelma ngomense); both species have prostrate stems and foul-smelling, cylindrical-campanulate, striated and dark-coloured flowers characteristic of a sapromyiophilous pollination strategy.